2015
DOI: 10.1093/ee/nvv158
|View full text |Cite
|
Sign up to set email alerts
|

Seed Predators, not Herbivores, Exert Natural Selection onSolidagospp.in an Urban Archipelago

Abstract: The effects of urbanization on biodiversity are well established, as a growing city will reduce the size and diversity of patches of native plants. Recolonization of old patches and discovery of new ones by arthropod herbivores should occur as predicted by island biogeography theory. Although colonization represents an increase in biodiversity, such arrivals may exert new forms of natural selection on plants through herbivory and seed predation. Using a single species of old-field aster (Solidago altissima L.)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 31 publications
1
9
1
Order By: Relevance
“…Our study has demonstrated that urbanization generally decreases the background damage of woody plants by leaf‐eating insects across multiple cities, tree species and herbivore feeding guilds. This pattern contrasts with the long‐standing belief about higher herbivory in urban habitats (Dreistadt et al., ) but agrees with more recent work, which frequently has reported a decrease in herbivory with urbanization, especially in terms of plant damage imposed by defoliating insects (Bode & Gilbert, ; Nuckols & Connor, ; but see Cuevas‐Reyes et al., ). The abundance of leafminers increased more frequently with urbanization when compared to the increase in defoliators (Raupp et al., ), but this pattern may differ between insect species (Rickman & Connor, ), thereby yielding a zero net effect (Nuckols & Connor, ).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Our study has demonstrated that urbanization generally decreases the background damage of woody plants by leaf‐eating insects across multiple cities, tree species and herbivore feeding guilds. This pattern contrasts with the long‐standing belief about higher herbivory in urban habitats (Dreistadt et al., ) but agrees with more recent work, which frequently has reported a decrease in herbivory with urbanization, especially in terms of plant damage imposed by defoliating insects (Bode & Gilbert, ; Nuckols & Connor, ; but see Cuevas‐Reyes et al., ). The abundance of leafminers increased more frequently with urbanization when compared to the increase in defoliators (Raupp et al., ), but this pattern may differ between insect species (Rickman & Connor, ), thereby yielding a zero net effect (Nuckols & Connor, ).…”
Section: Discussionsupporting
confidence: 84%
“…Patches of habitats suitable for wildlife tend to become smaller and more isolated with increases in urbanization (Luck & Wu, ), and the loss of habitat area generally results in a decrease in plant damage by insects (Bode & Gilbert, ; Rickman & Connor, ). Therefore, the possibility remains that habitat fragmentation has also contributed to the observed decrease in background insect herbivory in urban habitats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Urban production limitation can be affected at multiple stages, from the number of flowers produced to pre‐dispersal seed predation (eg Bode and Gilbert ), but research has mainly focused on the impact of urban drivers on pollen limitation. Pollen limitation may be due to changes in pollen quality and quantity, resulting in unfertilized flowers or self‐fertilization, which increases the risk of inbreeding depression.…”
Section: Evidence Of Urban Plant Recruitment Limitationmentioning
confidence: 99%
“…Seed removal and predation rates are reported to be higher in urban plant communities than in rural sites (Bowers and Breland ), though such trends may be species dependent (Pufal and Klein ). What drives these changes is less clear, but there is evidence that light pollution, fragmentation and patch size, and biotic invasion may alter the intensity and spatial patterns of seed predation (eg Bode and Gilbert ; Guiden and Orrock ). Other urban drivers, including pollutants such as nitrate and ammonium, may also modify seed bank dynamics and drive compositional shifts in seed bank populations (Pellissier et al .…”
Section: Evidence Of Urban Plant Recruitment Limitationmentioning
confidence: 99%